EXPLORING AESTHETIC VALUE: HOW IT MEASURED? DOES IT AFFECT THE SATISFACTION AND LOYALTY OF GALLERY VISITORS? (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Art galleries are one of the crucial infrastructures in the creative sector, serving as a platform to promote and develop the creative works of society for sustainable development. In the consumption of art galleries, aesthetic value plays a vital role, more than functional values, for gallery visitors. This study aims to develop a measurement tool for the construct of aesthetic value and test its influence on the satisfaction and loyalty of art gallery visitors. In the first study, a literature review on the concept was conducted and then used to create measurement tools and develop the conceptual model. Data from a survey of 242 art gallery visitors in Yogyakarta were analyzed with Exploratory Factor Analysis (EFA) to determine the number of factors retained in the concept. In the second study, the influence of aesthetic value on consumer satisfaction and loyalty (intention to revisit and intention to recommend) was tested. Survey data from 225 respondents were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the two studies revealed four dimensions representing Aesthetic Value: artwork, facility-place, knowledge, and emotion. Additionally, aesthetic value also influences consumer satisfaction and loyalty (intention to revisit and intention to recommend) in art galleries.
Keywords: aesthetic value; art gallery; scale measurement; satisfaction; loyalty